The concept of showing off on social media in the contemporary era: an analysis based on Imam Al Ghazali’s perspective - Saidin, Siti Nazirah; Alosman, Abdulrahman (Global Academic Excellence, 2024)
In contemporary era, social media plays a vital role in every aspect of society’s life. It tends to be a platform for people to share their daily life to the world just by clicking at fingertips. This study aims to explore the concept of showing off on social media among the students at International Islamic University Malaysia, to determine the concept of showing off from Imam Ghazali’s perspective and to analyze the effects of showing off towards Muslims' spirituality. The study used qualitative method by distributing online survey to 30 students in International Islamic University Malaysia (IIUM). The data was collected using an online questionnaire through Google Form. The main findings of this study showed that the act of showing off can be determined based on personal intention, showing off can be refer to riya’ in Arabic terms is considered as spiritual disease based on Imam Al Ghazali’s view and the impacts of showing off towards Muslim’s spirituality are can destroy someone’s self-esteem, lead to arrogance (takabbur), develop the feeling of envious or jealousy and distract Muslims from their spiritual practices and obligations